Perancangan Desain Interior Ruang Siaran Jelang Pemilu 2024 - Putra, Toni Wijanarko Adi; Santi Widiastuti; Widya Ariyani; Sulartopo; Budi Hartono; Khoirur Rozikin; Ayyub Hamdanu Budi Nurmana; Iman Saufik Suasana (Community : Jurnal Pengabdian Pada Masyarakat, 2024)
In carrying out television broadcast production, the activity organizer has a very important role. Good cooperation between personnel in this system is very necessary to achieve the desired broadcast production. The implementation of television broadcast production has a production working group. The production work group is a work unit that will handle production work together until the production is declared ready for broadcast. The work groups in television broadcasting include: Production/Broadcast Work Unit, Public Facilities Work Unit, Technical Operator Work Unit, Technician Work Unit.